Perioperative Management and Outcome of Bilateral Adrenalectomy in 9 Dogs. Issue 6 (11th July 2016) - Oblak, Michelle L.; Bacon, Nicholas J.; Covey, Jennifer L.
Abstract : Objective: To report perioperative care, postoperative management, and long‐term outcomes in dogs undergoing bilateral adrenalectomy. Study Design: Retrospective case series. Animals: Dogs undergoing bilateral adrenalectomy from 2008 to 2013 (n=9). Methods: Data retrieved from the record, when available, included signalment, preoperative clinical signs, laboratory data, diagnostic imaging, blood pressure measurement, preoperative treatment for adrenal gland disease, intraoperative procedures, treatments and complications, postoperative treatment and diagnostics during hospitalization, diagnostics and management following discharge, histopathologic diagnosis, and survival. Results: Seven dogs underwent concurrent bilateral adrenalectomy and 2 dogs had staged adrenalectomy. Surgery was uncomplicated in most cases. All dogs received IV dexamethasone SP intraoperatively. Eight dogs received intramuscular desoxycorticosterone pivalate intraoperatively. Histopathology revealed adrenocortical adenoma (7 dogs), adrenocortical carcinoma (4), pheochromocytoma (6), and adrenocortical atrophy (1). One dog died perioperatively and the remainder died due to unrelated causes. Postoperative management of hypoadrenocorticism included oral prednisone and intramuscular desoxycorticosterone pivalate (6 dogs), oral prednisone and fludrocortisone (1), and oral fludrocortisone alone (1). The median survival time in dogs surviving to hospital discharge was 525 days (range 67–966 days). No dogs developed metastatic disease or died due to signs of hypoadrenocorticism. Conclusion: Based on the cases reported here, the perioperative mortality in dogs undergoing bilateral adrenalectomy may be lower than previously reported. Management of postoperative hypoadrenocorticism is both achievable and straightforward.